Manajemen Mutu Pelayanan Pendidikan di MA Muslimat NU Palangkaraya - Anne Yuliana Sutisna (UNISAN JURNAL, 2024)
This research aims to explore the factors that influence the implementation of educational service quality in educational institutions. By using a qualitative approach and conducting in-depth analysis of the practices of implementing quality education services, data was collected through interviews, observations and documentation studies. The research results show that factors such as effective leadership, quality human resources, and relevant and innovative curriculum have a significant role in influencing the implementation of quality educational services. Implementation of good quality educational services has a positive impact on the quality of educational services provided, including increasing student involvement in the learning process and stakeholder satisfaction. In conclusion, it is important for educational institutions to pay attention to and manage these factors well in order to improve the implementation of the quality of educational services and achieve the desired educational goals. Keywords: Quality of Education Services